Southern Islands Vascular Flora (SIVFLORA) dataset: A global plant database from Southern Ocean islands - Guerrero, Pablo C.; Contador Mejias, Tamara Andrea; Diaz, Angie; Escobar, Catalina; Orlando, Julieta; Marin, Catalina; Medina, Patricio (My University, 2025)
The Southern Islands Vascular Flora (SIVFLORA) dataset is a globally significant, open-access resource that compiles essential biodiversity data on vascular plants from islands across the Southern Ocean. The SIVFLORA dataset was generated through five steps: study area delimitation, compiling the dataset, validating and harmonizing taxonomy, structuring dataset attributes, and establishing file format and open access. Covering major taxonomic divisions, SIVFLORA offers a comprehensive overview of plant occurrences, comprising 14,589 records representing 886 species, 95 families, and 42 orders. This dataset documents that 58.62% of the taxa are native, 9.61% are endemic, and 31.77% are alien species. The Falkland/Malvinas Archipelago, the most species-rich, contrast sharply with less diverse islands like the South Orkney Archipelago. SIVFLORA serves as a taxonomically harmonized, interoperable resource for investigating plant diversity patterns, ecosystem responses to climate change in extreme environments, island biogeography, endemism, and the effects of anthropogenic pressures on Southern Ocean flora.
Keywords: Flora; Vascular plant